PENGARUH PENERAPAN SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Listriana, Ulfa (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of the implementation of tax administration system to the tax compliance at KPP Pabean Cantikan Surabaya.The result of the research shows that the influence of the implementation of tax administration systems (Organization Procedure, Organization Strategy, and Organization Culture) simultaneously have significant to the tax compliance. The Organization Strategy variable shows that partially it has significant influence to the tax compliance. While the Organization Procedure and Organization Culture show that partially these variables have no significant influence to the tax compliance. Keywords: Tax Administration System, Tax Compliance, Organization Procedure, Organization Strategy, Organization Culture.